Transport costs, intermediate goods, and localized growth - Uwe Walz (Eberhard Karls Universität Tübingen, Wirtschaftswissenschaftliche Fakultät, 1993)
This paper constructs a dynamic two-regional general equilibrium model, in which the interregional production and trade patterns are endogenously determined. By embedding an endogenous growth mechanism in this approach, it becomes possible to show why and how localized growth with different regional growth rates may emerge without any locational limitations of technological spillovers and despite labor mobility. Geographical concentration of intermediate goods results from the interaction between transport costs and imperfect competition in the intermediate goods production process. Since growth stems from this sector, this also opens up the possibility of localized growth. Furthermore, the analysis sheds some light on the relation between the location of final goods and the geographical distribution of the intermediate inputs in the final goods.
Keywords: 330